2022
DOI: 10.3390/sports10010009
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Recovery of Well-Trained Younger and Older Athletes during Different HIIT Protocols

Abstract: Due to physiological and morphological differences, younger and older athletes may recover differently from training loads. High-intensity interval training (HIIT) protocols are useful for studying the progression of recovery. It was the objective of this study to determine age differences in performance and recovery following different HIIT protocols. Methods: 12 younger (24.5 ± 3.7 years) and 12 older (47.3 ± 8.6 years) well-trained cyclists and triathletes took part in this study. Between the age groups the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Our study is significant as it showed beneficial electroencephalographic changes in elderly patients after they performed the PEI program that included HIIT. Although task-specific electroencephalographic changes at the moment of performing specific cognitive domain tasks have been studied in young adult men after HIIT, 31 32 the post-interventional resting-state electroencephalographic effect of HIIT has not been elucidated. In general, resting EEG findings change with aging, with gradual alteration in the spectral power profile.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is significant as it showed beneficial electroencephalographic changes in elderly patients after they performed the PEI program that included HIIT. Although task-specific electroencephalographic changes at the moment of performing specific cognitive domain tasks have been studied in young adult men after HIIT, 31 32 the post-interventional resting-state electroencephalographic effect of HIIT has not been elucidated. In general, resting EEG findings change with aging, with gradual alteration in the spectral power profile.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more research is needed to establish the key age-related changes affecting the ventilatory responses. However, when comparing between well-trained younger (~ 24.5 ± 3.7 years old; 8 males, 4 females) and well-trained older adults (~ 47.3 ± 8.6 years old; 8 males, 4 females) there were no significant differences between post-exercise recovery kinetics [ 22 ]. These studies suggest that although aging leads to slower post-exercise recovery kinetics, exercise training status of an individual can mitigate this age-related decline which highlights the importance of maintaining regular exercise training across the lifespan.…”
Section: Introductionmentioning
confidence: 99%